Penerapan Metode Simple Additive Weighting (SAW) dalam Penentuan Bonus Karyawan (Studi Kasus: PT. Wana Anugrah Albasindo) - Zahirah, Regina Putri Wanda; Nadia Ayu Isroh; Prasetyo, Ade; Nur, Yohani Setiya Rafika (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET), 2024)
The agency will provide a salary as compensation for an employee's work. In addition to providing a basic wage, each agency often provides salary bonuses however, PT. Wana Anugrah Albasindo has difficulty distributing rewards to employees based on the performance of their employees, so decision support is needed based on the performance of each employee. The research data used criteria such as Presence, Number of Overtime Hours, and Length of Work. Based on the results and discussion of this research, it can be concluded that the application of determining employee bonuses with the SAW method is beneficial for PT. Wana Anugrah Albasindo is more transparent in deciding employee bonuses at PT. Wana Anugrah Albasindo determines the weight value of each assessment criterion in the form of attendance with a percentage of 50%, the number of overtime hours at 30%, and the length of work at 20%.